Experimenting with science in sports - Gardner, Robert, 1929- (New York : F. Watts, 1993)
Discusses how such principles of physics as force, gravity, and momentum apply to a variety of athletic actions, with experiments for the reader to try.
Athletes on the move -- Motion and sports -- Momentum, energy, and sports -- Lifts, curves, and bounces --Collisions in sports.
Includes bibliographical references (p. 123-124) and index.
Book Report.
Voice of Youth Advocates (V.O.Y.A.).
Wilson's Senior High School.
7-10.
Young Adult
Keywords: Physics -- Experiments -- Juvenile literature; Science -- Experiments -- Juvenile literature; Sports -- Juvenile literature; Experiments; Physics -- Experiments; Science -- Experiments; Sports; Physics -- Experiments; Science -- Experiments; Sports